2020
DOI: 10.15578/jppi.26.2.2020.109-123
|View full text |Cite
|
Sign up to set email alerts
|

Dinamika Perikanan Pelagis Kecil Dengan Pukat Cincin Di Perairan Samudera Hindia Barat Sumatera

Abstract: Sumberdaya ikan pelagis kecil hasil tangkapan pukat cincin di perairan Samudera Hindia Barat Sumatera memberikan kontribusi penting terhadap produksi perikanan di wilayah tersebut setelah ikan pelagis besar. Supaya pemanfaatannya berkelanjutan maka diperlukan upaya pengelolaan sumber daya ikan berdasarkan kajian perikanan dan biologinya. Data bulanan selama Maret sampai Desember 2018 dikumpulkan dari TPI Lampulo (Banda Aceh) dan Sibolga (Sumatera Utara), bertujuan untuk memperoleh informasi dan menganalisis te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 6 publications
0
3
0
4
Order By: Relevance
“…A similar pattern also appeared in the southern (Zedta et al, 2017) and eastern part of Indonesian waters (Nugraha & Mardlijah, 2017). However, it is still unclear how the mean length from Kutaraja was smaller than Sibolga when utilizing a similar configuration (Yusuf et al, 2020), probably due to the fishers in Kutaraja using the shorter version of the purse seine. In general, the average length size from all locations was relatively smaller than those collected from Pacitan, East Java (Yusuf et al, 2019) and Manado, North Sulawesi (Kekenusa et al, 2012), even though using the same gear type.…”
Section: Length Distributionmentioning
confidence: 54%
See 1 more Smart Citation
“…A similar pattern also appeared in the southern (Zedta et al, 2017) and eastern part of Indonesian waters (Nugraha & Mardlijah, 2017). However, it is still unclear how the mean length from Kutaraja was smaller than Sibolga when utilizing a similar configuration (Yusuf et al, 2020), probably due to the fishers in Kutaraja using the shorter version of the purse seine. In general, the average length size from all locations was relatively smaller than those collected from Pacitan, East Java (Yusuf et al, 2019) and Manado, North Sulawesi (Kekenusa et al, 2012), even though using the same gear type.…”
Section: Length Distributionmentioning
confidence: 54%
“…Estimated b values from both locations were higher than three as the threshold value, which indicated a positive allometry growth pattern (i.e., the incremental weight gain is more significant than its length). The similarities were likely caused by the indifferences in gear used, whereas Rahmah et al (2021); Rizwan et al (2014); Yusuf et al (2020) all confirmed that fishers from Sibolga and Kutaraja use almost identical purse seine configurations (including its mesh size). Thus, it's generated in a reasonably consistent catch size across the year of observations due to selectivity constraint, as shown in Table 1.…”
Section: Length Distributionmentioning
confidence: 94%
“…Penelitian Yusuf et al (2020) yang menyebutkan bahwa secara umum penangkapan ikan oleh kapal pelagis kecil pukat rapat di PPN Sibolga dilakukan di wilayah coastal dan teritorial Indonesia yang merupakan daerah sebaran ikan pelagis kecil di sekitar perairan Simeulue, Pulau Banyak, Pulau Nias. Sementara itu, apabila mengacu pada Peraturan Menteri Kelautan dan Perikanan Nomor 58 Tahun 2020, bahwa kapal penangkap ikan berukuran 30-100 GT diberikan daerah penangkapan ikan di perairan kepulauan dan ZEEI atau wajib > 12 mil.…”
Section: Hasil Dan Pembahasanunclassified
“…Hutapea et al (2023), menyebutkan bahwa sebanyak 85 % responden menyatakan kapal pelagis kecil pukat rapat di Sibolga menangkap ikan < 3 spesies dengan ukuran yang berbeda. Penelitian Yusuf et al (2020) Hasil dari skoring kriteria daerah penangkapan ikan (DPI) potensial pada purse seine pukat tongkol berukuran 30-100 GT pada Tabel 6, menunjukkan bahwa dominan responden dengan bobot tertinggi 5 berada pada 1 kriteria saja yaitu tingkat kesulitan menemukan spesies target dengan sub kriteria spesies target mudah ditemukan dan spot penangkapan relatif konstan. Alat tangkap purse seine dengan ukuran kapal 98 yang berpangkalan di PPN Sibolga, memiliki daerah penangkapan sejauh 70 mil dari pulau terluar Sumatera (Sari et al 2022).…”
Section: Hasil Dan Pembahasanunclassified
“…In comparison, fishing operations are carried out for 3-5 days in one fishing effort for gillnets. One of the factors that can affect fishing activities is the amount of fishing effort made by fishermen in reaching fishing areas [12]. The following is a breakdown of The development and increase in the production of fishing products is determined by several things, including the size of the ship, fishing technology, engine strength, and fishing aids.…”
Section: Production and Catching Effortmentioning
confidence: 99%